Possibly drug-induced palpable migratory arciform erythema - Fernando Luiz Teixeira Dantas; Neusa Yuriko Sakai Valente; Isis Suga Veronez; Priscila Kakizaki; Juliana Ribeiro Leitão; Rafael Cavanellas Fraga (Sociedade Brasileira de Dermatologia, 2015)
AbstractPalpable migratory arciform erythema is an entity of unknown etiology, with few published cases in the literature. The clinical and histopathological features of this disease are difficult to be distinguished from those of Jessner's lymphocytic infiltration of the skin, lupus erythematous tumidus and the deep erythema annulare centrifugum. We describe here the first two Brazilian cases of palpable migratory arciform erythema. The patients presented with infiltrated annular plaques and erythematous arcs without scales. These showed centrifugal growth before disappearing without scarring or residual lesions after a few days. They had a chronic course with repeated episodes for years. In addition, these cases provide evidence of a drug-induced etiology.